PERTANGGUNGJAWABAN PT. AEROFOOD INDONESIA UNIT DENPASAR TERHADAP SILOAM INTERNASIONAL HOSPITAL BALI TERKAIT KETIDAKSESUAIAN PELAYANAN PENYEDIAAN JASA MAKANAN - Alit Adnya Sari Dewi, Komang; Putrawan, Suatra (Kertha Semaya : Journal Ilmu Hukum, 2015)
The rise of private enterprise coorperating with other companies not deny a default or negligence committed by businesses and consumers themselves. In terms of coorperation in the event of any inconsistency in the agreement then one party would be disadvantaged. The purpose of this study was to determine the extent of liability of PT. Aerofood Indonesia as the manufacturer of the food service provider for the patient Siloam Hospital’s status as a consumer service mismatch related to food provision. The research method used is the juridical empirical method, which is a study of the real and factual circumstances that exist in the community or on the field. The conclusion of this paper is the responsibility of PT. Aerofood Indonesia Unit Denpasar toward the International Siloam Hospital in Bali related service provision foodservice discrepancy is the obligation of compensation set forth in the provisions of Article 3 of the 8 Provision of Food Services Cooperation Agreement and Article 1243 Code of Civil Law
Keywords: Accountability, Limited Liability Company, Partnership Agreement, Business Communities